Birnessite-type manganese dioxide nanoparticles embedded with nitrogen-doped carbon for high-performance supercapacitor. (December 2020) - Ahamad, Tansir; Naushad, Mu; Ubaidullah, Mohd; Alzaharani, Yahya; Alshehri, Saad M.
Highlights: Egg albumin was applied as precursor for preparation of NDC and MnO2 @NDC. As fabricated MnO2 nanoparticles are uniformly dispersed in N doped carbon matrix. The prepared MnO2 @NDC has high specific surface area and mesoporous structure. MnO2 @NDC shows good performance in asymmetric supercapacitor. Abstract: In this study, we have fabricated manganese oxide nanoparticles embedded with N-doped carbon (MnO2 /NDC) using egg albumin via hydrothermal and post calcination treatment. It was noticed that the MnO2 nanoparticles were grown into the nitrogen doped carbon matrix. As-fabricated NDC and MnO2 /NDC show excellent surface area about to 685 m 2 /g and 645 m 2 /g respectively. The SEM and TEM images results revealed that the fabricated birnessite-type MnO2 nanoparticles are uniformly embedded into N-doped graphitic carbon matrix. The asymmetric super capacitor cell (ASC) was fabricated using the NDC and MnO2 /NDC nanocomposites as a cathode and anode respectively and separated with whatman filter paper and 1.0 M Na2 SO4 was used as electrolyte. The specific capacitance of the asymmetric supercapacitor is determine and found 895 Fg −1 at 0.5Ag −1 current density. The fabricated ASC show excellent charge and discharge properties and long term stability. The asymmetric NDC//MnO2 /NDC cell supplies an excellent energy density about to 402.5 W h kg −1 with power density about to 2250 W kg −1 . Therefore, these outcomes support that fabricated nanocomposite can be used as a potential electrode material for supercapacitor application.